Intersections, Ambivalence, and Racial Justice in Schools: Black Queer Students Remap Complexity. Issue 14 (November 2018) - Mayo, Cris
This chapter analyzes retrospective interviews with Black LGBTQ college students discussing how their racial and LGBTQ identities intersected in high school. Their complex analysis shows the difficulties schools had recognizing the intersections between support for racial equity and LGBTQ-related equity. Their experience demonstrates the necessity of preparing educators and administrators to understand how many vectors of identity shape students' lives. Their narratives, too, show how Black community values and practices helped them to develop their sense of political advocacy on all issues, that traditions of civil rights advocacy gave them vocabularies for articulating new recognition and rights claims, and that longstanding forms of racialized sexual and gender identities were resources for their own rethinking of their commitments, even if they nonetheless did not always experience acceptance at schools or at home.